Fiscal federalism in theory and practice - Ter-Minassian, Teresa; International Monetary Fund. (Washington : International Monetary Fund, 1997)
This book is intended to contribute to the evolving body of knowledge by providing an overview of the current thinking in the literature on these issues (the theory of fiscal federalism) and the current status of intergovernmental fiscal relations in a broad range of industrial, developing, and transition economies (thepractice of fiscal federalism). As a reflection of the IMF's focus on macroeconomic issues, the book emphasized the macroeconomic dimensions of intergovernmental fiscal relations, an area that until recently had been relatively neglected in the fiscal federalism literature.
Papers prepared by the staff of the International Monetary Fund's Fiscal Affairs Dept.
Includes bibliographical references.
oif 16/07/14, opc 28/09/16
Loans
Keywords: Intergovernmental fiscal relations; Revenue sharing; Intergovernmental fiscal relations; Revenue sharing